Next-Generation Intestinal Toxicity Model of Human Embryonic Stem Cell-Derived Enterocyte-Like Cells - Ryu, Bokyeong; Son, Mi-Young; Jung, Kwang Bo; Kim, Ukjin; Kim, Jin; Kwon, Ohman; Son, Ye Seul; Jung, Cho-Rok; Park, Jae-Hak; Kim, C-Yoon (Frontiers in Veterinary Science, 2021)
The gastrointestinal tract is the most common exposure route of xenobiotics and, intestinal toxicity can result in systemic toxicity in most cases. It is important to develop intestinal toxicity assays mimicking human system, thus stem cells are rapidly being developed as new paradigms of toxicity assessment. In this study, we established human embryonic stem cell (hESC)-derived enterocyte-like cells (ELCs) and compared to existing in vivo and in vitro models. We found hESC-ELCs and in vivo model showed transcriptomically similar expression patterns of total 10,020 genes than commercialized cell lines. Asides, we treated the hESC-ELCs, in vivo rats, Caco-2 cells, and Hutu-80 cells with quarter log units of lethal dose 50 or lethal concentration 50 of eight drugs; chloramphenicol, cycloheximide, cytarabine, diclofenac, fluorouracil, indomethacin, methotrexate, oxytetracycline; then subsequently analyzed biomolecular markers and morphological changes. While the four models showed similar tendencies in general toxicological reaction, hESC-ELCs showed a stronger correlation with in vivo model than immortalized cell lines. These results indicate hESC-ELCs can serve as a next-generation intestinal toxicity model.